COAST Development Group's international consensus guidelines for the treatment of canine osteoarthritis - Cachon, Thibaut; Frykman, Ole; Innes, John F.; Lascelles, B. Duncan X.; Okumura, Masahiro; Sousa, Pedro; Staffieri, Francesco; Steagall, Paulo V.; Van Ryssen, Bernadette (Frontiers in Veterinary Science, 2023)
This report describes consensus guidelines and recommendations for the treatment of canine osteoarthritis (OA) according to the “Canine OsteoArthritis Staging Tool excluding radiography” (COASTeR) stage of OA, by the COAST Development Group. The recommendations are based on evidence-based medicine and clinical experience and are proposed with international relevance in mind. The aim is to provide veterinarians with a practical reference to consolidated information and to support the development of patient-specific OA management protocols and informed treatment choices based on the stage of OA.